Reorganization of social security and development of human capital - N. F. Chelukhina (Путеводитель предпринимателя)
The article describes the functions of social security and its role in minimizing the risks of human capital. Author stated goals and objectives pursued by economic actors in the management of these risks. There are the conclusions about the need to expand the social insurance system in Russia.